Pengadaan Barang/Jasa Melalui E-Catalogue di Lingkungan Perusahaan Umum Daerah (Perumda) Tirtanadi Sumatera Utara - Tanjung, Ahmad Feri; Sianturi, Ronald Hasudungan; Antoni, Jufri; Sagala, Frengky; Ichsan, Datuk Syahlafati (ARBITER: Jurnal Ilmiah Magister Hukum, 2025)
Procurement of goods/services is a crucial aspect in supporting company operations, particularly in ensuring the availability of facilities and infrastructure needed to run services optimally. This study aims to analyze the implementation of procurement of goods/services through the e-catalog system in the Regional Public Company (Perumda) Tirtanadi North Sumatra. E-catalog is a form of electronic procurement that is expected to increase efficiency, transparency, and accountability in the procurement process. The research method used is a qualitative approach with data collection techniques through in-depth interviews, observations, and documentation studies. The results show that the implementation of the e-catalog in Perumda Tirtanadi has been running in accordance with the regulations set by the Government Goods/Services Procurement Policy Agency (LKPP). However, in its implementation there are still several obstacles such as limited human resources who understand the e-catalog system thoroughly, delays in catalog updates by providers, and technical obstacles related to the network system. Nevertheless, the use of the e-catalog has a positive impact in reducing the potential for corruption, accelerating the procurement process, and facilitating monitoring and evaluation. Therefore, regular training and improvement of information technology infrastructure are needed to support the optimization of the e-catalogue-based procurement system within Perumda Tirtanadi.